PVAC dispersions for the gluing of weakened panel paintings - Gwendoline Firmery (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The abundant recent literature concerning PVAC dispersions and their properties has permitted us to take stock of advances in research on panel painting adhesives. Our study engages with the issues of stability and reversibility, both theoretical and practical, of PVAC dispersions, leading us to reconsider the advantages of their use over proteinic adhesives for opening damaged joints, in cases where swelling produced by the solvent could be problematic.